Preparation method of epsilon / delta-MnO2 composite material and formaldehyde patch prepared from epsilon / delta-MnO2 composite material

By mixing MnCl2 and KMnO4 in the solvent, adjusting the pH value and aging, the ε/δ-MnO2 composite material is prepared, which solves the inconvenience of use of existing formaldehyde removal products and may lead to secondary contamination, and achieves the effect of efficient formaldehyde removal at room temperature.

CN119746847AActive Publication Date: 2025-04-04JIANGHAN UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411950089.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing formaldehyde removal products have problems such as inconvenient use, limited scenarios, low energy utilization and possible secondary pollution. The energy utilization rate of traditional manganese dioxide preparation methods is not high, making it difficult to produce and apply on a large scale.

Method used

MnCl2 and KMnO4 are mixed in solvent, adjusted the pH to 0.9-1.3, and aged to prepare ε/δ-MnO2 composite material for the preparation of formaldehyde removal patches, which have the ability to degrade formaldehyde at room temperature and indoor photocatalyst.

Benefits of technology

It achieves efficient removal of formaldehyde at room temperature, excellent formaldehyde removal and conversion rate, avoids secondary pollution, and is also suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746847A_ABST
    Figure CN119746847A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an epsilon / delta-MnO2 composite material and a formaldehyde patch prepared from the epsilon / delta-MnO2 composite material, and belongs to the technical field of formaldehyde catalytic materials. The preparation method of the epsilon / delta-MnO2 composite material comprises the following steps: mixing MnCl2 and KMnO4 in a solvent to obtain a precursor solution, adjusting the pH value to be 1.3, and aging to obtain the epsilon / delta-MnO2 composite material. The epsilon / delta-MnO2 composite material prepared by the invention has excellent formaldehyde catalytic degradation capability at room temperature and under an indoor fluorescent lamp, and is excellent in formaldehyde removal rate and conversion rate. The prepared epsilon / delta-MnO2 composite material is prepared into a formaldehyde removal patch, so that the problems of inconvenience in use, limited use scene and the like of an existing formaldehyde removal product (such as a spray and the like) can be avoided, and the formaldehyde removal patch can be applied to different occasions and is flexible in use scene. The epsilon / delta-MnO2 composite material provided by the invention can remove formaldehyde at room temperature, and can completely catalyze and oxidize formaldehyde into carbon dioxide and water without causing secondary pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of formaldehyde catalytic materials, and in particular to a method for preparing an ε / δ-MnO2 composite material and a formaldehyde patch prepared using the same. Background Art

[0002] At present, formaldehyde, as an important harmful component of indoor pollution, mainly comes from building materials and furniture, and will pose a continuous potential threat to human health. Exposure to high-concentration formaldehyde environment can cause symptoms such as dizziness, tearing, allergies, bronchitis, leukemia, and even death in severe cases. In the 2017 list of carcinogens published by the World Health Organization's International Agency for Research on Cancer, formaldehyde is listed as a Class 1 carcinogen. Therefore, how to efficiently remove formaldehyde without causing secondary pollution has become an important focus of scientific research. However, although most of the catalysts prepared in previous studies have good catalytic degradation effects on formaldehyde, they usually require high temperature conditions, expensive precious metal (Pt, Au, Ag, Pd, etc.) loading, and high light intensity requirements, which bring great challenges to practical applications. Manganese dioxide has become the focus of current research due to its diverse crystal forms, multiple valence states, good low-temperature catalytic ability and excellent environmental compatibility. However, the traditional method of preparing manganese dioxide is mainly carried out by microwave, hydrothermal and other methods, with low energy utilization, which is not conducive to large-scale production and application.

[0003] The mainstream formaldehyde removal products on the market currently include spray formaldehyde removers, activated carbon, and filters used in conjunction with large equipment. Spray formaldehyde removers are mainly prepared by dissolving formaldehyde catalysts into solutions, and then effectively degrading formaldehyde in the air by spraying and atomizing. Although they are simple to use and have a certain effect on removing formaldehyde, they have many disadvantages. First, the release of formaldehyde is a long process, and spray formaldehyde removers can only reduce the formaldehyde content in the air in a short period of time, so frequent re-spraying is required. Secondly, the use of sprays depends largely on the uniformity and coverage of the spray, so when the spray is uneven, formaldehyde in some areas cannot be effectively removed. Furthermore, the tiny solid particles left by the spray after the water evaporates will cause particle pollution, and some chemical components will cause irreversible damage to biological and human health. In addition, long-term spraying of these high-solvent spray formaldehyde removers may also cause corrosion to furniture (wood and other components). At the same time, the use space of formaldehyde sprays will also be limited. For example, places such as kitchens and wardrobes that have zero contact with food, tableware, and skin are not suitable for use. As a simple formaldehyde adsorbent, activated carbon mainly removes formaldehyde through physical adsorption. It will reach adsorption saturation after a period of use. The adsorbed formaldehyde may be released back into the air to cause secondary pollution to the environment. Since adsorbents such as activated carbon only transfer formaldehyde in space, they cannot fundamentally remove formaldehyde. In addition, in a high heat and humidity environment, the adsorption performance of activated carbon will drop rapidly. The method of using filters and large air equipment to remove formaldehyde is expensive and occupies a large area. It can only be used in fixed locations and consumes a lot of electricity. Therefore, it is urgent to design a new formaldehyde removal product. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing an ε / δ-MnO2 composite material and a formaldehyde patch prepared therefrom, so as to solve the above-mentioned problems in the background technology. The ε / δ-MnO2 composite material prepared by the present invention has excellent ability to catalyze and degrade formaldehyde at room temperature and under indoor fluorescent lamps, and has excellent formaldehyde removal rate and conversion rate. The prepared ε / δ-MnO2 composite material is made into a formaldehyde removal patch, which can avoid the problems of inconvenient use and limited use scenarios of existing formaldehyde removal products (such as sprays, etc.), and can be pasted on different occasions, with flexible use scenarios. The ε / δ-MnO2 composite material of the present invention can remove formaldehyde at room temperature, and can completely catalyze and oxidize formaldehyde into carbon dioxide and water without causing secondary pollution.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is to provide a method for preparing an ε / δ-MnO2 composite material, which is characterized by comprising the following steps:

[0007] MnCl2 and KMnO4 are mixed in a solvent to obtain a precursor solution, the pH value is adjusted to pH=0.9-1.3, and the solution is aged to obtain the ε / δ-MnO2 composite material.

[0008] Preferably, the solvent is water.

[0009] Preferably, the molar ratio of MnCl2 to KMnO4 is 1.2:1.

[0010] The strong acid environment of the present invention can enhance the oxidizability of potassium permanganate, which is more conducive to the reaction. The present invention can ensure a more complete reaction by adding potassium permanganate in excess.

[0011] Preferably, the manganese ion concentration in the precursor solution is 0.12 mol / L.

[0012] Preferably, the pH is adjusted by adding hydrochloric acid.

[0013] Preferably, the aging temperature is 25-30°C and the time is 12-24h.

[0014] The second technical solution of the present invention is to provide an ε / δ-MnO2 composite material obtained according to the above preparation method.

[0015] The third technical solution of the present invention is to provide a formaldehyde sticker, which is obtained by fixing the above-mentioned ε / δ-MnO2 composite material on the outside of the sticker.

[0016] Preferably, the formaldehyde sticker comprises a sticker with adhesiveness on the inner side, the ε / δ-MnO2 composite material covering the outer side of the sticker, and a filter for fixing the ε / δ-MnO2 composite material.

[0017] The fourth technical solution of the present invention is to provide an application of the above-mentioned ε / δ-MnO2 composite material or formaldehyde patch in the field of formaldehyde removal.

[0018] Compared with the traditional hydrothermal method for preparing MnO2 materials, the present invention proposes a method for effectively synthesizing ε / δ-MnO2 at low temperature. The present invention uses MnCl2 as a raw material to prepare ε / δ-MnO2 with higher formaldehyde catalytic performance, and this product also has certain photocatalytic activity.

[0019] The formaldehyde sticker of the present invention can be customized into any shape, can be used in more complex environments, will not cause secondary pollution, will not affect human health, and is safer.

[0020] The beneficial technical effects of the present invention are as follows:

[0021] The ε / δ-MnO2 composite material prepared by the present invention has excellent catalytic degradation of formaldehyde at room temperature and under indoor fluorescent lamps, and has excellent formaldehyde removal rate and conversion rate. The prepared ε / δ-MnO2 composite material is made into a formaldehyde removal patch, which can avoid the problems of inconvenience and limited use scenarios of existing formaldehyde removal products (such as sprays, etc.), and can be pasted in different occasions, with flexible use scenarios.

[0022] The ε / δ-MnO2 composite material of the present invention can remove formaldehyde at room temperature, and can completely catalytically oxidize formaldehyde into carbon dioxide and water without causing secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 It is the XRD diagram of the products of Examples 1-3 and Comparative Examples 1-4.

[0025] Figure 2 The formaldehyde concentration change diagram of the products of Examples 1-3 and Comparative Examples 1-4 during the test process.

[0026] Figure 3 The graph is a graph showing the change in carbon dioxide concentration during the test of the products of Examples 1-3 and Comparative Examples 1-4.

[0027] Figure 4 This is a cycle test diagram of Example 2.

[0028] Figure 5 It is the UV-visible diffuse reflectance spectra of the products of Example 2 and Comparative Example 1 (the inset is the forbidden band width diagram of the products of Example 2 and Comparative Example 1).

[0029] Figure 6 The electrochemical impedance spectra of the products of Example 2 and Comparative Example 1 are shown.

[0030] Figure 7 The schematic diagram of the structure of the formaldehyde sticker of Example 4. Including: 1ε / δ-MnO2 composite material, 2 film net, 3 front sticker paper, 4 main body sticker.

[0031] Figure 8 It is a formaldehyde conversion performance diagram of the products of Examples 1-3 and Comparative Examples 1-4.

[0032] Fig. 9This is a real picture of the formaldehyde patch made from the ε / δ-MnO2 composite material of Example 2. DETAILED DESCRIPTION

[0033] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0034] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0035] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0036] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0037] The "room temperature" in the present invention is 10-30°C unless otherwise specified.

[0038] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.

[0039] Example 1

[0040] A method for preparing an ε / δ-MnO2 composite material, comprising the following steps:

[0041] 2.376 g MnCl2·H2O (0.012 mol) was weighed and placed in a beaker containing 100 mL ultrapure water and stirred for 10 min. Then 1.58 g KMnO4 (0.01 mol) was added and the pH value was adjusted to pH = 1.3 by adding hydrochloric acid. After sufficient stirring for 1 h, the stirrer was sucked out with a magnet and aged at 30 ° C for 12 h. After the aging, it was centrifugally cleaned with ultrapure water and ethanol in turn, and finally dried in an oven at 80 ° C for 18 h to obtain an ε / δ-MnO2 composite material.

[0042] Example 2

[0043] A method for preparing an ε / δ-MnO2 composite material, comprising the following steps:

[0044] 2.376 g MnCl2·H2O (0.012 mol) was weighed and placed in a beaker containing 100 mL ultrapure water and stirred for 10 min. Then 1.58 g KMnO4 (0.01 mol) was added and the pH value was adjusted to pH = 1.3 by adding hydrochloric acid. After sufficient stirring for 1 h, the stirrer was sucked out with a magnet and aged at 30 ° C for 18 h. After the aging, it was centrifugally cleaned with ultrapure water and ethanol in turn, and finally dried in an oven at 80 ° C for 18 h to obtain an ε / δ-MnO2 composite material.

[0045] Example 3

[0046] A method for preparing an ε / δ-MnO2 composite material, comprising the following steps:

[0047] 2.376 g MnCl2·H2O (0.012 mol) was weighed and placed in a beaker containing 100 mL ultrapure water and stirred for 10 min. Then 1.58 g KMnO4 (0.01 mol) was added and the pH value was adjusted to pH = 1.3 by adding hydrochloric acid. After sufficient stirring for 1 h, the stirrer was sucked out with a magnet and aged at 30 ° C for 24 h. After aging, it was centrifugally cleaned with ultrapure water and ethanol in turn, and finally dried in an oven at 80 ° C for 18 h to obtain an ε / δ-MnO2 composite material.

[0048] Comparative Example 1

[0049] A method for preparing an ε / δ-MnO2 composite material, comprising the following steps:

[0050] 2.028 g MnSO4·H2O (0.012 mol) was weighed and placed in a beaker containing 100 mL ultrapure water and stirred for 10 min. Then 1.58 g KMnO4 (0.01 mol) was added and the pH value was adjusted to pH = 1.3 by adding sulfuric acid. After sufficient stirring for 1 h, the stirrer was sucked out with a magnet and aged at 30 ° C for 18 h. After aging, it was centrifugally cleaned with ultrapure water and ethanol in turn, and finally dried in an oven at 80 ° C for 18 h to obtain an ε / δ-MnO2 composite material.

[0051] Comparative Example 2

[0052] A method for preparing an ε / δ-MnO2 composite material, comprising the following steps:

[0053] 3.012 g Mn(NO3)2·4H2O (0.012 mol) was weighed and placed in a beaker containing 100 mL ultrapure water and stirred for 10 min. Then 1.58 g KMnO4 (0.01 mol) was added and the pH value was adjusted to pH = 1.3 by adding nitric acid. After sufficient stirring for 1 h, the stirrer was sucked out with a magnet and aged at 30 ° C for 18 h. After aging, it was centrifugally cleaned with ultrapure water and ethanol in turn, and finally dried in an oven at 80 ° C for 18 h to obtain an ε / δ-MnO2 composite material.

[0054] Comparative Example 3

[0055] A method for preparing a delta-MnO2 catalyst comprises the following steps:

[0056] Weigh 20 mL of C2H5OH, put it into a beaker containing 80 mL of ultrapure water and stir for 10 min, then add 3.16 g of KMnO4 (0.02 mol), stir thoroughly for 1 h, remove the stirrer with a magnet, and place it at 30 ° C for 18 h. After aging, centrifuge it with ultrapure water and ethanol in turn, and finally dry it in an oven at 80 ° C for 18 h to obtain a δ-MnO2 catalyst.

[0057] Comparative Example 4

[0058] A method for preparing an ε-MnO2 catalyst comprises the following steps:

[0059] Weigh 9.45g Mn(NO3)2·4H2O, put it into a beaker containing 70mL ultrapure water, and stir until the solution is clear to obtain Mn(NO3)2 solution. Then dissolve 2.12g Na2CO3 in 70mL ultrapure water and drop it into the Mn(NO3)2 solution; then adjust the solution pH to 8, react at room temperature for 3h to obtain a white solid, centrifuge, and then dry it in an oven at 80℃ for 12h, then calcine the obtained white solid in a muffle furnace at a heating rate of 2℃ / min from room temperature to 350℃, and keep it at 350℃ for 4h to obtain ε-MnO2 catalyst.

[0060] Figure 1 It is the XRD diagram of the products of Examples 1-3 and Comparative Examples 1-4.

[0061] Depend on Figure 1It can be seen that the diffraction peaks corresponding to δ-MnO2 (JCPDS: 18-0802) and ε-MnO2 (JCPDS: 30-0802) can be found in Examples 1-3 and Comparative Examples 1-2, which indicates that the five samples are all ε / δ-MnO2 catalysts. However, Comparative Example 3 only has two weaker diffraction peaks at 36.8° and 65.7°, corresponding to the (006) and (119) crystal planes of δ-MnO2, respectively. This shows that Comparative Example 3 is composed only of δ-MnO2 and has poor crystallinity. In comparing the spectra of Examples 1-3 and Comparative Examples 1-2, a broad peak appears at 20° in Example 1-3, which is due to the overlap of the diffraction peak of δ-MnO2 at 18.6° and the peak of ε-MnO2 at 21°. Comparative Example 4 is the prepared monomer ε-MnO2, and Examples 1-3 all have diffraction peaks at around 56°, which further indicates that ε-MnO2 and δ-MnO2 exist simultaneously in Examples 1-3. And no obvious diffraction peak is observed at 18.6° in Comparative Example 1-2, which is mainly due to its poor crystallinity.

[0062] Example 4

[0063] A method for preparing a formaldehyde patch, comprising the following steps:

[0064] The ε / δ-MnO2 composite materials prepared in Examples 1-3 were ground evenly, and then the obtained catalyst powder was evenly laid on one side of the double-sided adhesive tape. Due to the adhesive effect, the catalyst powder was fixed on the double-sided adhesive tape. In order to prevent the catalyst powder from falling off, a microporous filter membrane with a pore size of 0.45 μm was sealed on the surface of the catalyst powder layer, so that while preventing the catalyst from falling off, air could quickly contact the catalyst, and a formaldehyde patch was prepared.

[0065] Fig. 9 This is a real picture of the formaldehyde patch made from the ε / δ-MnO2 composite material of Example 2.

[0066] Effect verification

[0067] Formaldehyde catalytic degradation experiment:

[0068] The performance of the catalysts prepared in Examples 1-3 and Comparative Examples 1-4 was tested in a 6L sealed chemical reactor lined with aluminum foil. The experimental steps are as follows: First, 0.1g of sample was evenly spread on the surface of a culture dish with a diameter of 9cm, and the interaction between the catalyst and formaldehyde was adjusted by opening and closing the cover; then treated with a desiccant and sodium hydroxide to adjust the initial concentrations of water and carbon dioxide to the same level as the experimental environment; then a syringe was used to inject a 38% formaldehyde solution into the system through the inlet, and a 5w fan was used to promote air circulation in the sealed chemical reactor. The light and dark environment were controlled by switching the fluorescent lamp inside the closed reactor. The test temperature was 25°C and the test duration was 36min. The test results are shown in Table 1.

[0069] Among them, the formula for formaldehyde removal rate is: (initial concentration-final concentration) / initial concentration.

[0070] The formula for formaldehyde conversion rate is: (final concentration of carbon dioxide - initial concentration of carbon dioxide) / initial concentration of formaldehyde.

[0071] Table 1 Removal and conversion efficiency of formaldehyde by samples under light / dark conditions

[0072]

[0073] Table 1 lists the formaldehyde removal efficiency and formaldehyde conversion efficiency of all samples under light and dark conditions. It can be seen that the formaldehyde removal efficiency of Examples 1-3 under dark conditions is 86.7%, 94.3% and 90.8% respectively, and the formaldehyde removal efficiency under light is 87.9%, 88.8% and 85.8%, which is significantly higher than the 84.3%, 80.7%, 55.2% and 38.7% of Comparative Examples 1-4 under dark conditions and 78.8%, 80.9%, 49.3% and 46.2% under light. Compared with the removal efficiency, the gap between the examples and the comparative examples in terms of formaldehyde conversion efficiency is even greater. The formaldehyde conversion efficiencies of Examples 1-3 under dark conditions were 67.8%, 73%, and 59%, respectively, and the formaldehyde conversion efficiencies under light conditions were 72.7%, 83.6%, and 70.1%, respectively, which were much higher than 44%, 38.5%, 0%, and 0% of Comparative Examples 1-4 under dark conditions and 63.5%, 41.7%, 1%, and 4.1% under light conditions. For the same example, the formaldehyde conversion efficiency under light conditions was higher than the formaldehyde conversion efficiency of the example under dark conditions. This shows that the example has good photocatalytic activity.

[0074] Figure 2 The formaldehyde concentration change diagram of the products of Examples 1-3 and Comparative Examples 1-4 during the test process.

[0075] Figure 3 The graph is a graph showing the change in carbon dioxide concentration during the test of the products of Examples 1-3 and Comparative Examples 1-4.

[0076] Figure 2 and Figure 3 The performance test chart of the prepared samples shows that the formaldehyde removal ability is as follows: Example 2> Example 1> Example 3> Comparative Example 1> Comparative Example 2> Comparative Example 3> Comparative Example 4, and the formaldehyde conversion ability is as follows: Example 2> Example 1> Example 3> Comparative Example 1> Comparative Example 2> Comparative Example 4> Comparative Example 3. Compared with other samples, Comparative Example 3 shows the worst formaldehyde removal ability. This is because Comparative Example 3 is only composed of δ-MnO2, and the pure phase δ-MnO2 has poor formaldehyde oxidation efficiency at 25°C, and the pure phase ε-MnO2 also shows poor catalytic activity, which also shows that the incorporation of ε-MnO2 interacts with δ-MnO2 and can effectively improve the formaldehyde catalytic performance of the catalyst of the present invention.

[0077] The above-mentioned formaldehyde catalytic degradation experimental conditions were used for the cycle experiment, and the results are shown in Figure 4 .

[0078] Figure 4 This is a cycle test diagram of Example 2.

[0079] Figure 4 The results show that Example 2 has good cycle stability and still maintains a high formaldehyde removal ability after four cycles.

[0080] Figure 5 It is the UV-visible diffuse reflectance spectra of the products of Example 2 and Comparative Example 1 (the inset is the forbidden band width diagram of the products of Example 2 and Comparative Example 1).

[0081] Depend on Figure 5 It can be seen that the DRS spectrum proves that the prepared MnO2 has a strong absorption capacity for the entire solar spectrum, and Example 2 has a stronger light absorption capacity than Comparative Example 1. In addition, according to the linear extrapolation method, it is found that the band gaps of Example 2 and Comparative Example 1 are 2.32 eV and 2.41 eV, respectively. Example 2 has a relatively narrower band gap, which is more conducive to light response and electron migration.

[0082] Figure 6 The electrochemical impedance spectra of the products of Example 2 and Comparative Example 1 are shown.

[0083] Depend on Figure 6 It can be seen that Example 2 has a smaller diameter, indicating that the charge transfer resistance is smaller, that is, the photogenerated electron-hole pairs are easier to separate and transfer. This is consistent with the phenomenon that the catalytic oxidation performance of the example under light conditions is significantly enhanced.

[0084] Figure 7 The schematic diagram of the structure of the formaldehyde sticker of Example 4. Including: 1ε / δ-MnO2 composite material, 2 film net, 3 front sticker paper, 4 main body sticker.

[0085] Figure 8 It is a formaldehyde conversion performance diagram of the products of Examples 1-3 and Comparative Examples 1-4.

[0086] Depend on Figure 8 It can be seen that the formaldehyde removal and conversion performance of each embodiment is higher than that of the comparative example, and under light conditions, the performance of the embodiment can be further improved.

[0087] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing an ε / δ-MnO2 composite material, characterized in that: The following steps are involved: MnCl2 and KMnO4 are mixed in a solvent to obtain a precursor solution, the pH value is adjusted to pH=0.9-1.3, and the solution is aged to obtain the ε / δ-MnO2 composite material.

2. The preparation method according to claim 1, characterized in that: The solvent is water.

3. The preparation method according to claim 1, characterized in that: The molar ratio of MnCl2 to KMnO4 is 1.2:

1.

4. The preparation method according to claim 1, characterized in that: The manganese ion concentration in the precursor solution is 0.12 mol / L.

5. The preparation method according to claim 1, characterized in that: The pH was adjusted by adding hydrochloric acid.

6. The preparation method according to claim 1, characterized in that: The aging temperature is 25-30°C and the time is 12-24h.

7. An ε / δ-MnO2 composite material obtained according to the preparation method according to any one of claims 1 to 6.

8. A formaldehyde sticker, characterized in that: The method is prepared by fixing the ε / δ-MnO2 composite material described in claim 7 on the outside of the sticker.

9. The formaldehyde patch according to claim 8, characterized in that: The formaldehyde sticker comprises a sticker with adhesiveness on the inner side, the ε / δ-MnO2 composite material covering the outer side of the sticker, and a filter for fixing the ε / δ-MnO2 composite material.

10. Use of the ε / δ-MnO2 composite material according to claim 7 or the formaldehyde patch according to claims 8-9 in the field of formaldehyde removal.

Citation Information

Patent Citations

  • Method for preparing manganese dioxide nano rod at low temperature

    CN102070196A

  • Preparation method and application method of manganese dioxide adsorbent

    CN103920448A

  • Delta-MnO2 catalytic material, preparation method thereof and application of delta-MnO2 catalytic material in preparation of filter screen capable of degrading formaldehyde

    CN116212853A

  • Aquaculture system that can be operated as water flow having filtering function

    KR102743323B1